CLINICAL, LABORATORY, AND MICROBIOLOGICAL CHARACTERISTICS OF PATIENTS WITH SEPTIC ARTHRITIS TREATED IN THAI NGUYEN (Vietnam Journal of Community Medicine, 2026)
Objective: To describe the clinical, laboratory, and microbiological characteristics of patients with septic arthritis who were hospitalized in the Department of Rheumatology, Thai Nguyen National Hospital, and the Department of Internal Rheumatology, A Thai Nguyen Hospital, during the period 2022–2025.Subjects and Methods: A cross-sectional descriptive study was conducted on 104 patients with septic arthritis who were treated as inpatients at the Department of Rheumatology, Thai Nguyen National Hospital, and the Department of Internal Rheumatology, A Thai Nguyen Hospital, from April 2022 to June 2025.Results: The mean age was 61.9 ± 11.6 years, with males accounting for 75.0%. The most common route of infection was post-intra-articular injection, representing 31.7%. Fever was present in 76.0% of patients. Infections most frequently involved the lower extremity joints (73.1%), with the knee being the most commonly affected joint, accounting for 59.2% among lower extremity joints. All patients (100%) presented with inflammatory-type joint pain. Joint swelling, warmth, and erythema were observed in 96.2% of cases. Leukocytosis was found in 76.9% of patients, and all patients (100%) showed elevated erythrocyte sedimentation rate after 1 hour. On plain radiography, joint abnormalities were detected in 38.5% of cases. Ultrasonography revealed joint effusion and synovial hypertrophy in 99.0% of patients.Synovial fluid analysis showed elevated leukocyte counts in all cases, with 56.5% exhibiting synovial fluid leukocyte counts ≥ 50,000 cells/mm³. Gram stain was positive in 30.8% of patients. Positive synovial fluid culture was observed in 46.2% of cases, with methicillin-resistant Staphylococcus aureus (MRSA) accounting for 50% of isolates.Conclusion: Septic arthritis predominantly occurs in elderly male patients. Prior intra-articular injection is the most frequently encountered risk factor. Clinically, patients typically present with pronounced inflammatory arthritis, most commonly affecting the lower extremity joints, particularly the knee. Laboratory findings usually reveal elevated inflammatory markers. MRSA is the most common causative pathogen. Definitive diagnosis is based on synovial fluid analysis in conjunction with clinical findings.
Keywords: Septic arthritis, MRSA